MENINGKATKAN KREATIVITAS DAN HASIL BELAJAR IPA SISWA KELAS VIII MTs. YAPPI JETIS SAPTOSARI GUNUNGKIDUL MELALUI PENGGUNAAN MEDIA ALAT PERAGA IPA - Rahman Afriyanto; Widowati Pusporini (Universitas Sarjanawiyata Tamansiswa, 2017)
The purpose of this research was to determine the learning process IPA through the use of the science props, so as to enhance the creativity and learning outcomes of science students of class VIII MTs.YAPPI Jetis Saptosari Gunungkidul the academic year 2016 / 2017. This type of research is the Classroom Action Research (CAR). The results showed that after learning through of the science props, creativity and learning outcomes IPA increased. This can be demonstrated by an increase in average based on the percentage of studentsâ€™ creativity observation sheet for each cycle, in the first cycle 21,67%Â and the second cycle 62,50%. Based on the results of tests of learning with the science props seen before by the action and after getting action. Improving students learning occurs on the average value of the capability is 56,68 increased to 74,42 at the end of the first cycle and increased again to 86,83 at the end of the second cycle. It can be concluded that learning IPA through the use of the science props can improve creativity and students learning outcomes.